Isolation and Characterization of Bacillus thuringiensis Isolated - Jabbar F. Al-maadhidi (Journal of Madenat Alelem University College, 2010)
Six isolates of Bacillus thuringiensis named BTA1, BTA2, BTA3, BTA4, BTA5 and BTA6 were adopted from ten isolates obtained from 15 different agriculture habitat samples, using special spore-enhancement method. It was found that these isolates produce very large-sized crystalline protein, which showing differences in shape under phase-contrast microscopy. Total genomic DNA of such isolates showed presence of mega plasmids, ringing from 70 to 125 MD, on fractionation by conventional agarose electrophoreses. The insecticidal activity (Bioassay) of these isolates against Ephestia larvae showed the isolates BTA1, BTA4, BTA5 and BTA6 have no pathogenic effects, and no hemothytic activity against human and sheep erythrocyte.